Analysis of Output Tax Calculation in Pharmaceutical Wholesale Trade: Case of PT Effata Fajar - Cici Ardina Prayitno Putri; Erry Andhaniwati (Jurnal Riset Perpajakan: Amnesty, 2024)
Although there are many other industries that bring in money for the country, such as oil and gas, export-import, and international aid, Indonesia is one of the countries that reports taxes every year and makes up the largest part of the state budget. Taxes are used to finance development carried out by the government in a country, such as infrastructure development, managing education and health. In taxation there is an output tax carried out by Taxable Entrepreneurs (PKP) who sell goods or services.  Sales is an important aspect for a company. Pharmaceutical companies, such as those listed on the Indonesian stock exchange, also have an important role in generating income through sales. Pharmaceutical Wholesale Trade (PBF) is the activity of buying and selling medicines and medical devices in large quantities carried out by a pharmaceutical company. Output VAT is calculated by multiplying the delivery price of medicines by a rate of 11%. Input VAT is calculated by multiplying the reimbursement price of medicines and medical devices by a rate of 11%. The use of tax invoices is included in the pharmaceutical wholesale trade aspect. These tax invoices are used as proof of transactions and as a basis for calculating output VAT. Every transaction involving the delivery of drugs and medical equipment requires a tax invoice from the pharmaceutical company, which can be completed online using an e-invoicing program. Unpaid value added tax known as output tax is what is required to be collected by Taxable Entrepreneurs (PKP) who provide Taxable Goods (BPK), Taxable Services (JKP), tangible BKP exports, intangible BKP exports, and exports JKP. Law Number 42 of 2009 concerning PA regulates output tax.